Life Cycle Assessment (LCA) of oyster farming in Washington State - Pucylowski, Teressa (2017)
Thesis (Master's)--University of Washington, 2017-06 Oysters are a culturally and economically valuable source of food and often promoted as an environmentally sustainable food choice. Life-cycle assessment (LCA) provides a standardized means of assessing the environmental costs of a product but has not previously been applied to oyster production. This thesis develops and applies an LCA for a production system in the Pacific North West (PNW), where oyster farming represents a major part of aquaculture production. Contemporary PNW oyster production typically consists of a hatchery, Floating Upweller System (FLUPSY), grow-out, and processing subsystems. LCA was used to quantify a suite of global scale resource depletion and environmental impacts of single-seed oyster aquaculture (individually grown instead of cultched), from cradle to retail-gate, using five different impacts categories: global warming potential (GWP), ozone depletion potential (ODP), marine eutrophication potential (MEP), human toxicity potential (HTP), and cumulative energy demand (CED). Two varieties of Pacific oysters (Crassostrea gigas) were analyzed using a functional unit (FU) of one dozen live oysters on the half shell: beach-grown oysters (trade name Classic Pacifics) and tide-tumbled oysters (trade name Shigokus). Results show electricity and fuel as the dominant contributors to impacts, with infrastructure, water use, and chemicals as minimal contributors. The contribution of each subsystem to total resource demand varied with each impact category. Production of Shigokus had slightly higher impacts overall, due to higher material use during the grow-out phase compared to Classic Pacifics, even though they have a higher survival rate. As a non-intensive and non-fed system, oyster aquaculture overall had low values per each impact category, confirming claims that they are a low environmental impact food choice.